REJECTION OF RELIGIOUS PHENOMENON IN KANT AND ITS REHABILITATION BY MARION - Kulangara, George (Journal of Dharma, 2010)
When philosophy turns its critical investigation towards religion, the philosopher has an unenviable task at hand. For, religion presents a veritable minefield of issues before which philosophy betrays its impotence. Religious phenomena like supernatural revelation, the Transcendent, etc. are not objects proper to philosophy at all if Kant has his way regarding the conditions of the possibility of experience of objects. Much of what goes on under religion should then be treated in history, sociology and psychology of religion and not in philosophy of religion. Kant held that any prospective candidate of phenomenon should appear in space and time as well as be guided by the categories of understanding. This is to say that a phenomenon should don an empirical garb. Kant is loath to yield an inch to so-called supra-empirical phenomena that crowd the domain of religion. “He came to what was his own, and his own people did not accept him” (John 1:11) – this Johannine regret referring to the rejection of Jesus at the hands of Jewish authorities as well as common people gives expression to the rejection of the claims of religious phenomena of all hues at the doorstep of critical philosophy of Kantian strand.